Peripheral Mechanisms of Dental Pain: The Role of Substance P - Paola Sacerdote; Luca Levrini (Hindawi Limited, 2012)
Current evidence supports the central role of neuropeptides in the molecular mechanisms underlying dental pain. In particular, substance P, a neuropeptide produced in neuron cell bodies localised in dorsal root and trigeminal ganglia, contributes to the transmission and maintenance of noxious stimuli and inflammatory processes. The major role of substance P in the onset of dental pain and inflammation is increasingly being recognised. Well-grounded experimental and clinical observations have documented an increase in substance P concentration in patients affected by caries, pulpitis, or granulomas and in those undergoing standard orthodontic or orthodontic/dental care procedures. This paper focuses on the role of substance P in the induction and maintenance of inflammation and dental pain, in order to define future lines of research for the evaluation of therapeutic strategies aimed at modulating the complex effects of this mediator in oral tissues.